Primary hydatid disease of sacrum affecting the sacroiliac joint - a case report - Yilmaz, N; Ozgocmen, S; Kocakoc, E; Kiris, A (Lippincott Williams & Wilkins, 2004)
Study Design. A case report of hydatid disease of the spine. Objective. To describe an unusual case of hydatid disease of the sacrum affecting the sacroiliac joint and to discuss imaging, differential diagnosis, and treatment. Summary of Background Data. Hydatidosis or echinococcosis affecting the spine is rare and has a characteristic geographic distribution. Signs of sacroiliac joint involvement and accompanying neurologic deficits cause difficulties in differential diagnosis of this rare condition. Methods. A case of 38-year-old female patient with low back pain and sciatica was presented. Results. Plain radiographs, computed tomography, and magnetic resonance imaging scans revealed destructive expansive lesion located on the right sacrum and extended through the right sacroiliac joint. Surgical enucleation of the cysts was performed together with mebendazole treatment and histopathologic examination confirmed hydatidosis. Conclusion. This unusual disease should be kept in mind in the differential diagnosis of sacroiliac pain and sciatica, especially in endemic areas.
Keywords: hydatid disease; echinococcosis; sacrum and sacroiliac joint